The The Role of the French Immigrant and Merchant Antonio Voulet in Paraná: immigrant Entrepreneurship, Networks of Sociability, and Capital Convertibility (TEL Tempo, Espaço e Linguagem, 2025)
This article explores the presence and activities of a small commercial bourgeoisie formed by French immigrants in Paraná at the end of the 19th century, focusing on the figure of Antonio Voulet, the owner of a renowned restaurant in Curitiba. Based on periodicals from the time, A República, O Dia, and Paraná Moderno, the article discusses the public presence of this proprietor and entrepreneur, the services and products he offered, and the social networks he established with both immigrants and non-immigrants in the urban space. The study aims to demonstrate how the accumulation of capital (P. Bourdieu) throughout his professional career and migratory trajectories, as well as his transnational connections and integration into social networks in Curitiba, were mobilized by French immigrants like him in the development of the gastronomy and hospitality sectors in Paraná. The research highlights the importance of studying the press to understand the socioeconomic, political, and cultural dynamics involving immigrants in urban contexts, which are often overlooked by the historiography of immigration in Paraná, and aims to contribute to the study of French immigrants.